Worry about the economic situation of the family in Italy: input from surveys conducted by the Observatory on Family Consumption Strategies - Tronca, Luigi (Italian Sociological Review, 2012)
This paper addresses the issue of worry about the future economic situation of the family by analysing data collected in 2009, 2010 and 2011 from samples of individuals resident in Italy by the Osservatorio sulle Strategie di Consumo delle Famiglie (Observatory on Family Consumption Strategies). After providing a theoretical overview of the object of study, I will attempt to establish whether the number of subjects who are worried about their family’s future economic situation increased between 2009 and 2011. After observing this rise, I will explore whether it has had more impact on those who have fewer available resources. The data analysis highlights that the increase in the sense of worry about future economic wellbeing is now actually more uniform with regard to the attributive qualities of individuals, tending to become a constant feature of their behavioural tendencies